Zanthoxylum rhoifolium and its potential for dendrochronological studies in the peruvian Amazon - Portal-Cahuana, Leif Armando; Huamán-Guevara, Rolando Majeed; Colina-Nano, Héctor Cesar (Ciência Florestal, 2023)
The study of the species that present dendrochronological potential is important and is the basis for more complex investigations that help to understand forests through dendrochronological techniques. We evaluated the dendrochronological potential of the species Zanthoxylum rhoifolium Lam.. In a high terrace forest in the Madre de Dios region of Peru. For this purpose, 10 trees of Zanthoxylum rhoifolium were used, of natural occurrence in the El Bosque farm of the National Amazonian University of Madre de Dios - UNAMAD, the collection was carried out through the non-destructive method with the help of the Pressler´s drill. Growth rings were characterized in the cross-section of the species, their dendrochronological potential, the relationship of the chronology with the local climate (precipitation and temperature), and the sea surface temperature (SST) HadlSST1. The results of the anatomical characterization of the growth rings of the species of Zanthoxylum rhoifolium, showed great potential for studies in dendrochronology because they present a good delimitation of the tree ring. A 32-year chronology (1985-2017) was built. Finally, it was possible to verify that the species Zanthoxylum rhoifolium, presented a significant response to the local climate and influence on SST.